ZOONOTIC SOIL-TRANSMITTED HELMINTHS: A TRIAD OF WORMS, ANIMALS, AND HUMANS AND THE VETERINARIAN’S ROLE IN COMMUNITY PUBLIC HEALTH - Glaum, Deborah (My University, 2015)
Although mankind has known about intestinal parasites for millennia, it has only been in the last century that scientists have recognized the diseases caused by zoonotic parasites. Soil-transmitted helminths (STHs), including Toxocara canis and Ancylostoma caninum, are an important subset of zoonotic parasites, and they have developed unique characteristics that allow them to infect humans and animals. Overt parasitism is no longer common in many developed nations; however, the subtle and varied symptoms associated with STH infection, along with the lack of experience and interest of the human healthcare industry, mean that many cases of zoonotic infection are missed. These diseases not only affect the health of humans, but they also have poverty-promoting effects. The lack of attention paid to these parasites in recent years has caused the World Health Organization to label them “neglected zoonotic diseases.” Human culture and individual behaviors are important risk factors for these diseases, as well as climate and geography. It will take a multidisciplinary approach to address zoonotic parasitic diseases, and veterinarians will have to engage as part of the community public health team, in order to make these efforts successful.
Keywords: Zoonotic diseases; Soil-transmitted helminths; Public health; Veterinary medicine; Multidisciplinary; Public Health (0573)